PREPARATION AND CHARACTERIZATION OF CURCUMIN NANOEMULSIONS OBTAINED BY THIN-FILM HYDRATION EMULSIFICATION AND ULTRASONICATION METHODS - A.A. Ochoa (Revista Mexicana de Ingeniería Química, 2016)
Curcumin is a natural polyphenolic compound with potent anticancer, anti-inflammatory, and antioxidant activities. However, itsimprove the solubility and bioavailability of bioactive compounds; and compared with the traditional mechanical methods, ultrasound is a superior tool to obtain nanoemulsions with smaller and homogeneous globule size and physical stability. The goal of this study was to develop a curcumin nanoemulsion by ultrasonication, containing a high curcumin load, small droplet size and good physical stability. The composition and preparation method effects on entrapment efficiency, droplet size, polydispersity index, and zeta potential of the nanoemulsions were evaluated. Curcumin nanoemulsions were successfully prepared by combined thin-film hydration emulsification and ultrasonication methods, employing 50 % of glycerol in the aqueous phase, and 10 % of soybean lecithin as emulsifier; at 20 % amplitude for 12 min in the sonicator. Nanoemulsions with 2.5 mg curcumin per g, 100 % entrapment efficiency, mean droplet size of 108 nm, and stable for 120 days at 4°C were obtained.